COVID-19 epidemiology and potential treatments: follow up interview - Baric, Ralph (Henry Stewart Talks, 2020)
More precise estimate of the mortality rate, What is the actual proportion of infected patients?, Why does the mortality rate vary so much between countries?, ‘Infectious dose’ or ‘number of viruses’ versus ‘viral load’, Recent clinical trial results for SARS-2 treatments and vaccines, Current clinical trials in Europe and the US